2017
DOI: 10.1371/journal.pone.0169343
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Out-of-Body Experience Reduces Fear of Death

Abstract: Immersive virtual reality can be used to visually substitute a person’s real body by a life-sized virtual body (VB) that is seen from first person perspective. Using real-time motion capture the VB can be programmed to move synchronously with the real body (visuomotor synchrony), and also virtual objects seen to strike the VB can be felt through corresponding vibrotactile stimulation on the actual body (visuotactile synchrony). This setup typically gives rise to a strong perceptual illusion of ownership over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 42 publications
1
96
1
3
Order By: Relevance
“…The type of a virtual body can have an effect on participant's experience of body-ownership and the behavior (Gorisse et al, 2019). These effects of virtually embodying a body other than one's own have been extensively explored: taller avatars would argue more aggressively (Yee et al, 2009), slimmer avatars have smaller body image (Serino et al, 2016); the cognitive effects are shown in increased connection to nature after embodying a cow (Ahn et al, 2016); stereotyping and biases get reduced when embodying an avatar of outer-group (Maister et al, 2015), stereotyping against elderly is reduced when embodying an older avatar (Yee and Bailenson, 2006), likewise embodying an other-race avatar reduces racial biases (Peck et al, 2013;Banakou et al, 2016;Hasler et al, 2017), while having a virtual out-of-body experience reduces the fear of death (Bourdin et al, 2017). Notably, becoming homeless in VR elicits long lasting (up to 8 weeks) positive attitudes toward homeless and increases the chances that participants will sign a petition for affordable housing (Herrera et al, 2018).…”
Section: Evidence Of Transformative Powers Of Vrmentioning
confidence: 99%
“…The type of a virtual body can have an effect on participant's experience of body-ownership and the behavior (Gorisse et al, 2019). These effects of virtually embodying a body other than one's own have been extensively explored: taller avatars would argue more aggressively (Yee et al, 2009), slimmer avatars have smaller body image (Serino et al, 2016); the cognitive effects are shown in increased connection to nature after embodying a cow (Ahn et al, 2016); stereotyping and biases get reduced when embodying an avatar of outer-group (Maister et al, 2015), stereotyping against elderly is reduced when embodying an older avatar (Yee and Bailenson, 2006), likewise embodying an other-race avatar reduces racial biases (Peck et al, 2013;Banakou et al, 2016;Hasler et al, 2017), while having a virtual out-of-body experience reduces the fear of death (Bourdin et al, 2017). Notably, becoming homeless in VR elicits long lasting (up to 8 weeks) positive attitudes toward homeless and increases the chances that participants will sign a petition for affordable housing (Herrera et al, 2018).…”
Section: Evidence Of Transformative Powers Of Vrmentioning
confidence: 99%
“…Experiencing the implicit survival beyond death should according to TMT result in an impact on the world view of participants to be less defensive of symbolic survival categories such as defence of their nation. Third, following on from our own previous work, where we found evidence that a simulated OBE results in a reduction of death anxiety [ 27 ], we were interested in whether those findings would be reproduced in a more complex scenario, where participants witnessed the simulated deaths of others, as well as experiencing their own NDE, and an implicit model of survival beyond death.…”
Section: Introductionmentioning
confidence: 98%
“…Initial results suggest that this could reduce other forms of suffering, such as that associated with the fear of death. 6 In the social domain, people can interact within a shared virtual space using representations of their own bodies recorded via so-called motion capture technologies. 7,8 This makes it possible to modify multiple aspects of the ongoing dyadic interactions in realtime.…”
Section: Introductionmentioning
confidence: 99%